Experimentální ověření ejektoru a vytvoření matematického modelu. - Strmiska, Michal (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Diplomová práce se zabývá problematikou ejektorů. V úvodu je tento stroj zařazen mezi hydraulické stroje. Je uveden princip a použití tohoto stroje. V další části jsou popsány dva rozdílné způsoby výpočtu a je navržen způsob konstrukce charakteristik určených výpočtem pomocí programu MS Excel. Úkolem práce je konfrontace těchto výsledků s experimentem prováděným ve Školní laboratoři Oboru Fluidního inženýrství Victora Kaplana. Popis experimentu a postup vyhodnocení naměřených hodnot je popsán v druhé části této práce.

This diploma thesis deals with the area of ejectors. In the intoduction, an ejector is classed as an hydraulic machine. There is also an introduction of the principle and application of this machine there. The next part describes two different ways of calculation and there is a suggestion how to get characteristics, that were achieved by calculation in MS Excel, projected. The purpose of this diploma thesis is to confront this mathematical model with the experiment done in school laboratory at Kaplan department of hydraulic machines. The description of this experiment and the evaluation procedure of measured values is described in the final part of this diploma thesis.
Experimental verification of ejector and creation of mathematical model.
Keywords: Ejektor; tryska; savka; proudové čerpadlo; Ejector; nozzle; diffuser; flow; jet; pump